Studying the Stability of one of Non-Linear Autoregressive Models with Application - Abdulghafoor Salim (Al-Rafidain Journal of Computer Sciences and Mathematics, 2011)
In This paper we suggest one of the models for non-linear Autoregressive by using local linear approximation method, then we studied the conditions of stationarity of the model specifically the conditions of stationarity the non-zero singular point of the model. And the conditions for stationarity to limit cycle stationarity. Conditions are applied in the aforementioned theories on data represent the monthly average wind speed in model of Baghdad city. The samples are classified by using  one of non-linear Autoregressive model the findings are the value of non-zero fixed point and the conditions of suggested stationarity model .